(untitled) (Argos, 2016)
The ancient biographers used different narrative forms but generally their intention was to describe the character and the personality of the people whose lives they were recounting. The problem examined in the article regards the role assigned by the biographers, on the one hand, to somatic features and the inherited character, on the other hand, to the education and the active construction of the character by the individuals.